Energy Balance of Smart Ventilated Facade - Salajka, Radek (Vysoké učení technické v Brně,Fakulta stavební, 2024)
This article explains the function and basic energy balance for a smart facade system that is being researched at Brno University of Technology. This system is an upgrade to an already well-known ventilated facade. The upgrade is mainly presented by efficient control over built-in shut-off dampers inside the ventilated gap. The main goal is to reduce the energy consumption of buildings and create a healthy and comfortable indoor thermal microclimate in a much more ecological way. Numerical calculations are being used to present the energy use of a given facade in comparison with other conventional facade systems on the same building with identical boundary conditions. FSVM software which provides these calculations has been developed by the same research team. It can calculate the energy balance of conventional facades, ETICS and prototype of smart facades as well. This article presents ongoing research and results of the simulation of the heat flow of these three main facade systems throughout the year. Significant variables for facade heat flow calculations are weather and outdoor boundary conditions. They are used in this article as conditions for the Czech Republic which has a mild climate and four different seasons of the year.
Keywords: Ventilated facade; smart facade; energy balance; ventilated gap; numerical simulation